2013
DOI: 10.1080/00015458.2013.11680923
|View full text |Cite
|
Sign up to set email alerts
|

Previous Bariatric Surgery Increases Postoperative Morbidity after Sleeve Gastrectomy for Morbid Obesity

Abstract: SG can be safely performed but patients and surgeons must be aware of a higher risk of postoperative complications when SG is proposed as a revisional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…Gagniere et al [24] reported a series of 102 patients undergoing primary or secondary LSG, with significantly higher risk for complications in the secondary LSG group. Germanova et al reported similar results [29]. The actual reported larger series shows that secondary LSG is associated with increased risk for major complications, although not statistically significant, probably because of sample size.…”
Section: Discussionsupporting
confidence: 68%
“…Gagniere et al [24] reported a series of 102 patients undergoing primary or secondary LSG, with significantly higher risk for complications in the secondary LSG group. Germanova et al reported similar results [29]. The actual reported larger series shows that secondary LSG is associated with increased risk for major complications, although not statistically significant, probably because of sample size.…”
Section: Discussionsupporting
confidence: 68%
“…Multiple studies have documented the increased risk of postoperative morbidity after revisional bariatric surgery [15][16][17][18]. There is also data suggesting higher reoperative rate for complications in patients undergoing revisional surgery [19].…”
Section: Discussionmentioning
confidence: 98%
“…Since absorbable membranes are expensive, they could be reserved to a specific population, at higher risk of developing complications. While leak risk factors are well studied [5][6][7][8][9], hemorrhage risk factors are not well established. In addition to the most commonly accepted leak risk factors (such as BMI > 50 kg/m 2 , severe sleep apnea, diabetes, age over 60, and previous gastric surgery), we have chosen two other potential risk factors for bleeding: hypertension and anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that may increase the leak risk have already been studied [5][6][7][8][9][10]. Some of these factors, such as body mass index (BMI) >50 kg/m 2 , previous gastric surgery, and the use of a calibration tube smaller than 40 F, have been correlated to increased risks of leaks and possible bleeding.…”
Section: Introductionmentioning
confidence: 99%